Rights And Obligations Husband Towards Wife in Islam (A Maudhu’I Hadith Study) - Yassinta Ananda; Rivaldi Amir (International Journal of Research, 2024)
Husband and wife relationship is the main pillar in household life. Islam regulates the rights and obligations of husbands and wives in a balanced manner to create a family that is sakinah, mawaddah, and warahmah. This research aims to analyze the rights and obligations of husbands towards wives in the perspective of hadith, focusing on maudhu'i hadith studies. This research uses a qualitative method with a maudhu'i (thematic) approach. Primary data were obtained from the traditions on the rights and obligations of husbands towards their wives referred to in the books of miftah kunuz al-sunnah or mu'jam al-muhfahras li alfadz al-hadith, while secondary data were obtained from relevant previous scientific research. Data analysis was conducted using the descriptive-analytic method. The results show that Islam gives balanced rights and obligations to husbands and wives. The husband's rights towards his wife include maintenance, obedience, and maintaining the husband's honor. The husband's obligations towards his wife include leading the family, protecting, and providing affection. Within the perspective of rights and duties, a variety of interpretations are found that can affect the practice of daily life. The correlation between the maudhu'i traditions and the implementation of the rights and duties of husbands towards wives is also a concern, where a proper understanding of Islamic teachings can form the basis for a balanced and respectful relationship. Thus increasing the awareness of both husband and wife about their respective rights and obligations. And help in building a household life that is sakinah, mawaddah, and warahmah